RUANG DALAM ARSITEKTUR BERWAWASAN PERILAKU - Rieka Angkouw; Herry Kapugu (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2012)
This paper examines how an architect designing a building, especially in the interior are not just based on his own imagination, but also pay attention to human behavior as a user. The assessment starts from the design of the architecture design of modern movement influenced by the lack of attention to the man himself as a user, but only focused on the architect and design objects, where as the behavior or the behavior of human beings who need to be considered in the design, especially in the formation of the space, so the design produced will be beneficial to humans. Keywords: Interior, in space, human behavior.